2022
DOI: 10.1155/2022/2630864
|View full text |Cite
|
Sign up to set email alerts
|

CircINTS4 Facilitates Chemoresistance of TNBC by Competitively Binding miR-129-5p/POM121 Axis

Abstract: Objectives. To detect the expression of circular RNA (circRNA) circINTS4 in triple-negative breast cancer (TNBC) and to analyze the relationship between the expression of circRNA circINTS4 and the clinicopathological characteristics and chemotherapy resistance of patients with TNBC. Methods. Bioinformatics was used to predict that circINTS4 and POM121 could bind to miR-129-5p, and dual luciferase reporter genes proved that circINTS4 could bind to miR-129-5p and miR-129-5p could bind to POM121. RNA immunoprecip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The limited choices of medical treatment for them are usually chemotherapy and immunotherapy but with limited therapeutic effect. Therefore, there is still a tremendous unmet need for the development of novel therapeutics for TNBC [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The limited choices of medical treatment for them are usually chemotherapy and immunotherapy but with limited therapeutic effect. Therefore, there is still a tremendous unmet need for the development of novel therapeutics for TNBC [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There were three studies published in 2019 (Liang et al, 2019; Ma et al, 2019; Yang et al, 2019), five studies published in 2020 (Dou et al, 2020a; Liu et al, 2020; Yang et al, 2020; Zang et al, 2020; Zhang, Su, et al, 2020), 10 studies published in 2021 (Hao et al, 2021; Huang et al, 2021; Li, Xia, et al, 2021; Li, Xu, et al, 2021; Ni et al, 2021; Wang, Liang, et al, 2021; Wang, Zhou, et al, 2021; Wu et al, 2021a; Zheng et al, 2021; Zhu et al, 2021a), eight studies published in 2022 (Chen, Shi, et al, 2021; Cui et al, 2022; Huang et al, 2022; Tang et al, 2022; Wang, Chen, et al, 2022; Wang, Shan, et al, 2022; Wang, Yang, et al, 2022; Xie & Zheng, 2022), and one study published in 2023 (Xu et al, 2023). Fourteen of the studies (Chen, Shi, et al, 2021; Cui et al, 2022; Dou et al, 2020a; Hao et al, 2021; Li, Xia, et al, 2021; Li, Xu, et al 2021; Liang et al, 2019; Tang et al, 2022; Wang, Chen, et al, 2022; Wang, Liang, et al, 2021; Wang, Shan, et al, 2022; Xie & Zheng, 2022; Xu et al, 2023; Zhang, Su, et al, 2020) were on adriamycin (ADM) resistance, nine studies (Huang et al, 2022; Li, Xu, et al, 2021; Liu et al, 2020; Ma et al, 2019; Ni et al, 2021; Wang, Zhou, et al, 2021; Yang et al, 2020; Zang et al, 2020; Zheng et al, 2021) were related to paclitaxel (PTX) resistance, two were related to 5‐fluorouracil (5‐FU) resistance (Yang et al, 2019; Zhu et al, 2021a), two studies were related to cisplatin resistance...…”
Section: Resultsmentioning
confidence: 99%
“…(Dou et al, 2020a;Liu et al, 2020;Yang et al, 2020;Zang et al, 2020;Zhang, Su, et al, 2020), 10 studies published in 2021(Hao et al, 2021;Huang et al, 2021;Li, Xu, et al, 2021;Ni et al, 2021;Wang, Liang, et al, 2021;Wang, Zhou, et al, 2021;Wu et al, 2021a;Zheng et al, 2021;Zhu et al, 2021a), eight studies published in 2022(Chen, Shi, et al, 2021;Cui et al, 2022;Huang et al, 2022;Tang et al, 2022;Wang, Chen, et al, 2022;Wang, Shan, et al, 2022;Xie & Zheng, 2022), and one study published in 2023(Xu et al, 2023). Fourteen of the studies(Chen, Shi, et al, 2021;Cui et al, 2022;Dou et al, 2020a;Hao et al, 2021;Li, Xu, et al 2021;Liang et al, 2019;Tang et al, 2022;Wang, Chen, et al, 2022;Wang, Liang, et al, 2021;Wang, Shan, et al, 2022;Xie & Zheng, 2022;Xu et al, 2023;Zhang, Su, et al, 2020) were on adriamycin (ADM) resistance, nine studies(Huang et al, 2022;Li, Xu, et al, 2021;Liu et al, 2020;Ma et al, 2019;…”
mentioning
confidence: 99%
“… 27 Tang et al indicated that circINTS4 confers chemotherapy resistance in breast cancer via competitive binding miR-129-5p/POM121 signaling axis. 28 Moreover, Chen et al reported that CircSCAP interacts with SF3A3 to restrain the malignant progression of non-small cell lung cancer via activating p53 signaling. 29 circAGFG1 is a poorly studied circRNA, and no studies have been reported in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%